Analisis Faktor Pengaruh Kualitas Audit Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Ryakaren, Sean Fileas; Claudia, Gita (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
OJK Regulation 29/POJK.4/2016 requires issuers to submit annual financial reports and imposes sanctions on violators, this encourages the growth of public accounting services. This study aims to analyze the effect of audit report lag, audit rotation, audit fee, and company size on audit quality in manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. The method used is logistic regression with secondary data from the financial statements of 324 manufacturing company observations. The results of the study indicate that audit report lag has a negative and significant effect on audit quality, indicating that the longer the audit time, the lower the audit quality due to potential problems in the financial statements. In contrast, audit rotation, audit fee, and company size do not have a significant effect on audit quality. The Nagelkerke R Square value of 0.148 shows that audit report lag, auditor rotation, audit fees and company size are able to explain audit quality by 14.8% and there are 85.2% other variables outside the model that can explain audit quality.These findings indicate that internal company factors and auditor competence play a greater role in determining audit quality than external factors such as auditor rotation or the amount of audit fees. This study provides a practical contribution by suggesting companies to focus on audit process efficiency, technology implementation, and strengthening internal control. From a theoretical perspective, these results support agency theory which emphasizes the importance of auditor independence and competence in producing quality audits. Further research is recommended to explore other variables, such as audit technology and internal control effectiveness, as well as expand research subjects outside the manufacturing sector.